Comparative Analysis of Egg Yolk Phospholipid Unsaturation and Its Impact on Neural Health in Alzheimer Disease Mice - Yuhang Sun; Yao Wu; Bing Fang; Jingyu Li; Yue Liu; Haina Gao; Ming Zhang (Foods)
The mechanism of egg yolk phosphatidylcholine (PC) in alleviating Alzheimer’s disease (AD) has not yet been clear. The fatty acid composition of PC, especially the ratio of polyunsaturated fatty acids (PUFA), may be a critical determinant of their structural and functional roles. This study aimed to conduct a comparative analysis of the unsaturation levels of egg yolk PC and their impact on neurological health in a murine model of AD. The results showed that oral administration of high and low unsaturation PC (HUP, LUP) enhanced learning and memory abilities in AD mice, with the HUP intervention demonstrating superior efficacy compared to the LUP. Follow-up biochemical analysis of the brain tissue also suggested that HUP intervention effectively mitigated oxidative-stress damage and inhibited tau hyperphosphorylation in AD mice. Meanwhile, lipidomic analyses of the mouse hippocampus revealed that HUP intervention substantially increased the levels of phospholipids, such as PEt (phosphatidylethanol) and BisMePA (bis(methylthio)phenylacetic acid), which are recognized as vital components of neuronal cell membranes. Furthermore, HUP intervention markedly elevated the levels of phospholipids incorporating PUFAs in the hippocampus. These results revealed a mitigating role for unsaturated egg yolk PC in AD prevention and offer new insights into AD prevention from a lipidomic perspective.